Finite element simulation of broadband biosonar signal propagation in the near- and far-field of an echolocating Atlantic bottlenose dolphin (Tursiops truncatus) - Wei, C.; Au, W.; Ketten, Darlene; Zhang, Y. (Acoustical Society of America, 2018)
© 2018 Author(s). Bottlenose dolphins project broadband echolocation signals for detecting and locating prey and predators, and for spatial orientation. There are many unknowns concerning the specifics of biosonar signal production and propagation in the head of dolphins and this manuscript represents an effort to address this topic. A two-dimensional finite element model was constructed using high resolution CT scan data. The model simulated the acoustic processes in the vertical plane of the biosonar signal emitted from the phonic lips and propagated into the water through the animal's head. The acoustic field on the animal's forehead and the farfield transmission beam pattern of the echolocating dolphin were determined. The simulation results and prior acoustic measurements were qualitatively extremely consistent. The role of the main structures on the sound propagation pathway such as the air sacs, melon, and connective tissue was investigated. Furthermore, an investigation of the driving force at the phonic lips for dolphins that emit broadband echolocation signals and porpoises that emit narrowband echolocation signals suggested that the driving force is different for the two types of biosonar. Finally, the results provide a visual understanding of the sound transmission in dolphin's biosonar.